Common Mistakes in Bone and Soft Tissue Tumors - Van Herck, Matthieu; Vanhoenacker, Filip M.; Verstraete, Koenraad (Seminars in Musculoskeletal Radiology, 2025)
Accurate diagnosis of bone and soft tissue tumors is critical for effective management, yet radiologic errors remain a significant challenge and may lead to inappropriate interventions or delays in adequate treatment. This article describes common radiologic mistakes encountered in evaluating these tumors, including key errors such as mischaracterizing benign versus malignant lesions, overreliance on single imaging modalities, and failure to integrate clinical and histopathologic data. We focus on imaging features that help differentiate benign from malignant lesions. The article also highlights situations in which imaging alone cannot help with accurate differentiation.
Keywords: mistakes; bone tumors; soft tissue tumors; radiography; magnetic resonance imaging